Unfinished Business: Democracy in Namibia - Koep, Monica; Sims, Bryan M. (Book collections on Project MUSE., 2012)
Idasa's Democracy Index - initially developed for South Africa - is being expanded into Southern Africa in an effort to broaden the capacity of individuals and organisations monitoring and supporting democratic governance efforts in the region. This inaugural Democracy Index for Namibia is intended to set a benchmark for democracy to be measured against. The tool assesses the country's depth of democracy through five focus areas: participation, elections, accountability, political rights, and human dignity. The research relies on expert analysis to answer a set of questions that interrogate how closely, in practice, democracy meets the broad ideal of self-representative government. More specifically, to what extent can citizens control elected officials and government appointees who make decisions about public affairs? And how equal are citizens to one another in this accountability process? The purpose of the scores is to assist citizens in making their own judgements, based on the information made available, to stimulate national debate and to provide democracy promoters with a tool for identifying issues and needs that can be addressed by education, advocacy, training, institution building and policy revision.